Digital Technologies are a Key Driver of the Development of Smart Cities: Analysis of World Rankings - G. G. Goloventchik (Цифровая трансформация)
A smart city is a system solution of actual urban problems through the use of the possibilities created by the latest achievements in the field of digital technologies. The article analyzes 15 world ratings of smart cities from the position of defining the priority areas of urban digitalization which in total become the drivers of the development of intelligent cities. The article gives a hybrid consensus-rating of top 25 smart cities of the world and reveals its connection with the level of digitalization of the country. The article shows that active use of innovative digital technologies helps smart cities more successfully overcome the consequences of the COVID-19 pandemic.